The Effective Use of Solid and Liquid Waste in Urban Agriculture - Majunder Bidisha; Jahowa Islam; Gangopadhyay Amitava (International Journal of Research in Chemistry and Environment (IJRCE), 2015)
Co-recycling of solid and liquid wastes is a common waste farming practice in urban agriculture. Long-term improper of wastes application deteriorate soil health due to nutrient enrichment and finally decline crop yield and cropping pattern. Little information is available on proper dosing of wastes in urban agriculture. The aim of this study was to determine the optimum application rate of solid and liquid wastes in a 100 years old existing waste farming area at Titagarh, India, to sustain soil health and crop productivity. The research was conducted with three pot trails on spinach, following the treatments: 1) Control, required N, P, K applied by 2) solid waste, 3) liquid waste, 4) combined solid and liquid waste, 5) Chemical fertilizers and 6) existing practice. Considering first trail results, the treatment of solid-liquid combination was found more significant in terms of the spinach yield, nutrient uptake by spinach and leaching loss. It was more confirmed after second trial and third trial, the combined application of solid-liquid waste (1:1), where 67% of required N dose for spinach was given by solid-liquid wastes, implicated highest yield and sustain soil health.